The effect of customer expectations and experience on satisfaction and repurchase intention on hijab products - Intani, Vidya; Rojuaniah , Rojuaniah (Institute of Computer Science (IOCS), 2024)
A Repurchase intention in marketing is generally a strong desire of consumers based on the experience of purchasing products that have been made in the past. When buying a product a customer has high expectations for the product they will buy, if the product purchased is as expected it will create a positive impression and make the customer have a good experience and will be satisfied with the product purchased. This study aims to analyze the effect of customer expectations and customer experience on customer satisfaction and repurchase intention. The population in this study is people who have purchased Zytadelia hijab products at least 1 time in the last 1 month in the Jabodetabek area with an age range of 20-40 years as many as 100 respondents. The method used in this study uses a quantitative approach by collecting data using a survey method by distributing questionnaires online. Data were analyzed using the SEM (Structural Equation Model) PLS method. Based on the analysis it was concluded that customer expectations have a positive effect on customer satisfaction, as well as customer experience have a positive effect on customer satisfaction. Apart from that, customer experience has a positive effect on repurchase intention, but customer expectations have no effect on repurchase intention. Furthermore, customer satisfaction has a positive effect on repurchase intentions. Customer satisfaction mediates customer expectations on repurchase intentions, has a positive and significant effect, and customer satisfaction mediates the effect of customer experience on repurchase intentions, has a positive and significant effect. The findings in this study are when customers buy Zytadelia hijab products and it meets their expectations or even exceeds them, a good impression will arise resulting in a good experience and will feel satisfied. When the customer is satisfied, there will be a desire to re-purchase Zytadelia hijab products.